Integration of linear alternators in thermoacoustic heat Engines - Abdelmwgoud, Moamen Bellah (AUC Knowledge Fountain, 2015)
A thermoacoustic power converter consists of a thermoacoustic heat engine driving a linear alternator connected to a matched electric load. Accordingly, linear alternators are essential parts of thermoacoustic power converters. However, integration of a linear alternator in a thermoacoustic power converter is complicated since it requires acoustic matching with the thermoacoustic engine as well as electrical matching with the electric load connected to it and fast protection against piston over-stroking. In order to simplify the integration process, an experimental setup designed and built, in which the acoustic power generated by a thermoacoustic engine simulated by an acoustic driver. This setup provides a platform to test and evaluate the performance of a linear alternator in a controlled environment before integrated into thermoacoustic heat engines that allows identification and resolution of potential problems only related to linear alternators. A control circuit designed and built to protect the alternator’s piston against over-stroking. A non-linear electric load connected to the alternator to provide a stable operating point of the complete system. In this setup, instrumentation is used to monitor the main variables (input and output current, input and output volt, dynamic gas pressure at exit of acoustic driver and inlet of linear alternator, dynamic gas pressure in the enclosure volume of the acoustic driver and linear alternator, acoustic driver stroke, linear alternator stroke, air and coil temperatures). The setup allows use of different resonators to simulate the effects of different front volumes on the performance of linear alternators and allows alterations in the enclosure volumes housing the acoustic driver and/or alternator to control their resonance frequencies. Results show the performance of a given linear alternator under different operating frequencies, mean gas pressure, gas mixtures, input voltage, electrical resistance and zener break-down voltage.